1988
DOI: 10.1017/s0950268800067212
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of rotavirus from feral pigeon in mammalian cell cultures

Abstract: SUMMARYAvian rotaviruses were isolated from feral pigeon faeces treated with trypsin using roller tube cultures of mammalian cells. Two pigeon strains, designated as strains PO-8 and PO-13, produced a marked cytopathic effect (CPE), small intracytoplasmic inclusion bodies and high titres of infectious particles in infected MA-104 and MDBK cell lines without cell adaptation and roller drum apparatus. The pigeon rotaviruses shared a common group specific antigen with the Lincoln strain of bovine rotavirus by ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
60
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 30 publications
1
60
0
Order By: Relevance
“…Since rotavirus infection in avian species was first reported in 1977, it became prevalent among several species of domesticated birds (Hines et al, 1995;McNulty and Reynolds, 2008;Minamoto et al, 1988). Rotaviruses isolation from bovine, porcine and human had been reported in Korea (Park et al, 2006;Jeong et al, 2009;Oh et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Since rotavirus infection in avian species was first reported in 1977, it became prevalent among several species of domesticated birds (Hines et al, 1995;McNulty and Reynolds, 2008;Minamoto et al, 1988). Rotaviruses isolation from bovine, porcine and human had been reported in Korea (Park et al, 2006;Jeong et al, 2009;Oh et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Some animal rotaviruses can bind to the cell either through interactions mediated by VP8 or VP5 via SA-containing and SA-independent cell surface receptors, respectively [7,24]. Human strains appear to use an SA-independent route [6], and an α2β1 integrin-binding motif (DGE) present in VP5 at amino acids 308-310 may function as the receptor-binding site [23].Rotaviruses have also been isolated from several avian species [15,16]. Previous studies have suggested that avian rotaviruses separated from mammalian rotaviruses early during evolution [10,11].…”
mentioning
confidence: 99%
“…However, it is not known whether avian rotaviruses can enter cells and infect animals by the same mechanisms as those by which mammalian rotaviruses cause infection. To investigate the involvement of SA on the cell surface, we tested four avian rotavirus strains.The avian rotavirus strain PO-13 (G7, P[17]) was isolated from a pigeon in Japan [16] and was passaged 12 times in MA104 cells. Turkey rotavirus strains Ty-3 (G7, P[17]) and Ty-1 (G7, P [17]) and a chicken rotavirus, strain Ch-1 (G7, P[17]), isolated using chicken embryo fibroblast cells and/or chick kidney cells in the United Kingdom [15], were provided by McNulty, Veterinary Research Laboratories, Belfast, United Kingdom, and were passaged several times in MA104 cells in our laboratory.…”
mentioning
confidence: 99%
See 2 more Smart Citations